Proposal for a revised definition of dilated cardiomyopathy, hypokinetic non-dilated cardiomyopathy, and its implications for clinical practice: a position statement of the ESC working group on myocardial and pericardial diseases - Pinto, Yigal M; Elliott, Perry M; Arbustini, Eloisa; Adler, Yehuda; Anastasakis, Aris; Böhm, Michael; Duboc, Denis; Gimeno, Juan; de Groote, Pascal; Imazio, Massimo; Heymans, Stephane; Klingel, Karin; et al. (European heart journal, 2016)
In this paper the Working Group on Myocardial and Pericardial Disease proposes a revised definition of dilated cardiomyopathy (DCM) in an attempt to bridge the gap between our recent understanding of the disease spectrum and its clinical presentation in relatives, which is key for early diagnosis and the institution of potential preventative measures. We also provide practical hints to identify subsets of the DCM syndrome where aetiology directed management has great clinical relevance.
Keywords: Dilated cardiomyopathy; dilatační kardiomyopatie; Early Diagnosis; Cardiomyopathy, Dilated; myokarditida; Pedigree; rodokmen; Risk Factors; Cardiomyopathies; Heart failure; Diagnosis, Differential; kardiomyopatie; Multimodal Imaging; Position statement; Myocarditis; lidé; multimodální zobrazování; Humans; diferenciální diagnóza; časná diagnóza; rizikové faktory